The Image of Trees in Folklore: Genesis and Poetic Interpretations - Kizi, Rustamova Gavkhar Bakhron (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the genesis of the image of trees in folklore, mythology, and artistic interpretations of folklore. It is known that each nation has its own way of life. In folklore, this originality is notable for its artistic expression. It is noteworthy that they contain motives and images typical of the epic tradition. In the system of images in folklore, the interpretation of religious views related to the image of trees has a special place. Such trees include poplar, willow, maple, spruce, willow, cypress, pine, walnut, mulberry, juniper and others. The depiction and interpretation of the image of the tree in epic and lyrical works seems to be based on the ancient mythological notions of our ancestors related to totemism. Well-known scientists, such as E. Taylor, J. Fraser, D. Zelenin, who studied the totemistic beliefs of primitive people, especially recognized the folk beliefs, ideas, views on the cult of plants in relation to trees, plants and flowers. reached. The genetic roots of images associated with trees are very complex. Because they still have faith in mythological cults. They are based on the totemistic ideas of primitive people and their beliefs about the plant and world.